BREAKING OF DORMANCY AND SPROUTING OF SOME POTATO (Solanum Tuberosum l.) VARIETIES UNDER DIFFERENT STORAGE CONDITIONS AND DURATIONS IN JOS, PLATEAU STATE, NIGERIA (FULafia Journal of Science and Technology, 2023)
A study was carried out at the National Root Crops Research Institute, Potato program (NRCRI) Kuru, Jos Plateau State, Nigeria (Longitude 08OE 47I, Latitude 09O N 44I and 1,239 meters above sea level (msl) during the 2010-2011, 2011-2012 and 2012- 2013 seasons to investigate “The Breaking of Dormancy and sprouting of some Potato (Solanum tuberosum L.) varieties under Different Storage Conditions and Durations in Jos, Plateau State, Nigeria”. Five potato varieties: Nicola, Bertita, Diamant, BR63-18 and Roslin Ruaka were stored for three periods: 12, 24 and 32 weeks in three types of stores, the Room temperature Store, Diffused light store (DLS) and Air conditioned store. The experimental design used was completely randomized design in factorial combination of 5 potato varieties, 3 storage conditions and 3 storage durations. There were 45 treatment combinations replicated 3 times. Weekly temperatures and Relative humidity were recorded in each type of store. The result showed that the number of days to breaking of Dormancy tubers varied with variety. In all the seasons, Nicola took the longest number of days to break dormancy (102.67, 121.33 and 119.00 days in seasons 1, 2and 3 respectively) while, BR63-18 was the earliest to break dormancy except in season 3 where Diamant was the first to break dormancy. Storage under Air condition took the longest number of days to break dormancy in all the seasons (85.67, 97.07 and 102.20 days in seasons 1, 2 and 3 respectively) while the Room temperature store was the earliest to break dormancy (67.66, 85.40 and 78.87 days in seasons 1, 2 and 3 respectively). The number of sprouted tubers varied with variety. Nicola resulted in the highest number of sprouted tubers in seasons 1 and 3 (35.56 and 33.85 respectively) while BR63-18 was highest in season 2. Storage under air condition resulted in highest number of sprouted tubers in seasons 1 and 3 (33.44 and 35.80 respectively). The number of sprouted tubers increased from 12 to 24 weeks and declined at 32 weeks in seasons 1 and 3. Seed tuber storage for 32 weeks resulted in significantly lower number of sprouted tubers in all the seasons. There was significant interaction of variety X store type, variety X storage duration and store type X storage duration with respect to number of sprouted tubers. The interaction may be attributed to genetic composition of the varieties and environmental conditions of the storage.
Keywords: Potato; storage conditions; storage durations; dormancy break and sprouting